Prevalência de nefropatia diabética e fatores associados em pacientes diabéticos tipo 2 de Estratégia Saúde da Família em município do sudoeste do Paraná - Carvalho Filho, Israel Gonçalves de (2023)
Type 2 diabetes mellitus is a highly prevalent disease in the world population and corresponds an important mortality rate in the adult population. This morbidity presents complications in target organs that increase the severity of the disease and diabetic nephropathy being one of these complications in its natural evolution. Diabetic nephropathy, a chronic kidney disease of diabetes, among its expected changes that is increased urinary albumin excretion or decreased glomerular filtration rate. These parameters are used for screening and diagnosing diabetic nephropathy in order to institute treatment for patients who have this complication. This study aimed to evaluate the prevalence of diabetic nephropathy in type 2 diabetic patients, the association of nephropathy with other risk variables and the variables that favored the development of diabetic kidney disease. For this, a quantitative cross-sectional study was carried out of the population served by the Family Health Strategy in a neighborhood in the municipality of Francisco Beltrão - Paraná. Patients over 18 years of age diagnosed with type 2 diabetes mellitus were admitted to the study, totaling 78 participants. Between May 2022 and February 2023, anthropometric data, laboratory tests and information on the use of antidiabetics, antihypertensives and statins were collected. Diabetic nephropathy was identified using glomerular filtration rate and albuminuria data. For analysis of associations, chi-square tests and binomial logistic regression were used. Mean values were verified for age (62.8 ± 11.7 years), body mass index (30.9 ± 5.1 Kg/m2), fasting blood glucose (159.6 ± 50.6 mg/dL ) and glycated hemoglobin (7.9 ± 1.9 %). The presence of nephropathy occurred in 30 individuals (38.5%). A positive association was found between diabetic nephropathy with urea > 40 mg/dL (X2=29.1, PR=4.32, p<0.001) and use of antihypertensive drugs (X2=3.87, PR=2.24, p=0.049). Glycated hemoglobin (OR 1.52, p=0.017) and urea (OR 1.16, p<0.01) were significant to determine, in parts, the presence of diabetic nephropathy. Was found mostly female, elderly, obese population, outside the glycemic and lipid target. Through this study, diabetic nephropathy could be diagnosed, revealing a prevalence of approximately 40%. The positive association of diabetic nephropathy in patients using antihypertensive medication, in addition to the greater risk of developing this complication in patients with high glycated hemoglobin, suggests that glycemic control associated whit lifestyle changes that seek to optimize morbidities, especially hypertension and obesity, must be established when developing preventive and therapeutic plans for the diabetic population.